Cystine and Methionine Deficiency Promotes Ferroptosis by Inducing B-Cell Translocation Gene 1 - Il-Je Cho; Doyeon Kim; Eun-Ok Kim; Kyung-Hwan Jegal; Jae-Kwang Kim; Sang-Mi Park; Rongjie Zhao; Sung-Hwan Ki; Sang-Chan Kim; Sae-Kwang Ku (MDPI AG, 2021)
Ferroptosis is a type of programmed necrosis triggered by iron-dependent lipid peroxidation. We investigated the role of B-cell translocation gene 1 (BTG1) in cystine and methionine deficiency (CST/Met (−))-mediated cell death. CST/Met (−) depleted reduced and oxidized glutathione in hepatocyte-derived cells, increased prostaglandin-endoperoxide synthase 2 expression, and promoted reactive oxygen species accumulation and lipid peroxidation, as well as necrotic cell death. CST/Met (−)-mediated cell death and lipid peroxidation was specifically inhibited by pretreatment with ferroptosis inhibitors. In parallel with cell death, CST/Met (−) blocked global protein translation and increased the expression of genes associated with the integrated stress response. Moreover, CST/Met (−) significantly induced BTG1 expression. Using a BTG1 promoter-harboring reporter gene and siRNA, activating transcription factor 4 (ATF4) was identified as an essential transcription factor for CST/Met (−)-mediated BTG1 induction. Although knockout of BTG1 in human HAP1 cells did not affect the accumulation of reactive oxygen species induced by CST/Met (−), BTG1 knockout significantly decreased the induction of genes associated with the integrated stress response, and reduced lipid peroxidation and cell death in response to CST/Met (−). The results demonstrate that CST/Met (−) induces ferroptosis by activating ATF4-dependent BTG1 induction.